2013
DOI: 10.1289/ehp.1205504
|View full text |Cite
|
Sign up to set email alerts
|

Possible Positive Selection for an Arsenic-Protective Haplotype in Humans

Abstract: Background: Arsenic in drinking water causes severe health effects. Indigenous people in the South American Andes have likely lived with arsenic-contaminated drinking water for thousands of years. Inhabitants of San Antonio de los Cobres (SAC) in the Argentinean highlands generally carry an AS3MT (the major arsenic-metabolizing gene) haplotype associated with reduced health risks due to rapid arsenic excretion and lower urinary fraction of the monomethylated metabolite.Objectives: We hypothesized an adaptation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 48 publications
0
37
1
Order By: Relevance
“…This gene frequency value is very high compared with an 8% found in populations living in non‐arsenical areas . We expect that similarly high gene frequencies will be observed in other regions where extreme levels of natural multi elemental contamination are present in the water sources . Thus, this gene most likely facilitated the peopling of endemic arsenical areas including the Andes.…”
Section: Adaptationmentioning
confidence: 61%
See 2 more Smart Citations
“…This gene frequency value is very high compared with an 8% found in populations living in non‐arsenical areas . We expect that similarly high gene frequencies will be observed in other regions where extreme levels of natural multi elemental contamination are present in the water sources . Thus, this gene most likely facilitated the peopling of endemic arsenical areas including the Andes.…”
Section: Adaptationmentioning
confidence: 61%
“…Antonio de los Cobres in Argentina and Camarones in Chile, areas, where arsenic levels in the water reach on average 300-1,000 μg/L, respectively, are able to metabolize and more quickly eliminate this semimetal from their bodies through urination. [81][82][83] Both populations present a 68% frequency of the AS3MT gene protective variant, which allows them to methylate arsenic and prevent poisoning. [81][82][83] This gene frequency value is very high compared with an 8% found in populations living in non-arsenical areas.…”
Section: Molecular Biology Data Indicates Modern Populations From Sanmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown marked differences in arsenic methylation patterns and genotypes based on ethnicity, and it is possible these caused the differences we identified [Engström et al, ; Fu et al, ]. Furthermore, the distribution of the protective AS3MT haplotype in the SAC population is higher than most populations around the world, making them extremely efficient arsenic metabolizers [Schlebusch et al, ]. Therefore, the contribution of N6AMT1 to arsenic metabolism within this population may differ from Chile.…”
Section: Discussionmentioning
confidence: 92%
“…This haplotype was associated with low %MMA and high %DMA, consistent with more efficient arsenic metabolism (Engström et al 2011). In the 34 women recruited in 2011, we genotyped AS3MT rs3740400, rs3740393, rs11191439, and rs1046778 with Taqman® SNP genotyping assays according to the manufacturer’s instructions, and inferred haplotype 2 based on the four SNPs only, as we have shown that we obtain very similar inferred AS3MT haplotypes with fewer SNPs compared with a larger number of SNPs (Schlebusch et al 2013). …”
Section: Methodsmentioning
confidence: 99%